Answer:
x=5 y=-6
Step-by-step explanation:
3x+y=9 ------eqn1
y=4-2x -------eqn2
using substitution
put y=4-2x into eqn1
3x+4-2x=9
x=5
put x=5 into eqn2
y=4-2(5)
y=4-10
y=-6
Let the fist integer be x, the second is x+20
the product of the numbers is:
x(x+20)
the sum of the numbers is:
x+x+20=2x+20
the sum of the above operations will give us:
2x+20+x^2+20x=95
x^2+22x+20=95
this can be written as quadratic to be:
x^2+22x-75=0
solving the above we get:
x=3 and x=-25
but since the integers should be positive, then x=3
the second number is x+20=3+20=23
hence the numbers are:
3 and 23
So we factor 12
remember that (-) times (-)=(+)
and
(-)+(-)=(-) so therefor the factors must be negative
factor 12
2,2,3
we have
-2 times -6 which adds to -8
-3 times -4 wihch adds to -7
the numbers are -3 and -4
V2^2 = V1^2 - 2gh
<span>=> 0 = 44^2 - 2 (32.2) h </span>
<span>=> h = 44^2 / 64.4 = 30.062 ft</span>
Answer:
6767676766767676776767677676767676677676767676767
Step-by-step explanation:
76767676767676767676767676767676767676767676767676